Anionic Copolymerization of Styrene Sulfide with Elemental Sulfur (S8) - Jakub Wręczycki (Materials, 2020)
The superior ability of thiiranes (episulfides) to undergo ring-opening polymerization (ROP) in the presence of anionic initiators allows the preparation of chemically stable polysulfide homopolymers. Incorporation of elemental sulfur (S8) by copolymerization below the floor temperature of S8 permits the placement of a large quantity of sulfur atoms in the polysulfide mainchain. The utility of styrene sulfide (2-phenylthiirane; StS) for copolymerization with elemental sulfur is reported here. A few polysulfides differing depending on the initial ratio of S8 to StS and copolymerization time were synthesized. Various spectroscopic methods (1H NMR, 13C NMR, Raman spectroscopy and FTIR spectroscopy) were applied to characterize the chemical structure of the copolymers. Additionally, the phase structure and thermal stability of the synthesized polysulfides were investigated using DSC and TGA, respectively. The successful anionic copolymerization of styrene sulfide and elemental sulfur has been demonstrated.